Effect of Cryopreservation on Pluripotency Gene Expression in Ehrlich Carcinoma Cells of Different Terms of Development - Chelombitko, Olga V.; Bondarovich, Nikolay A.; Ostankov, Maksim V.; Dimitrov, Aleksey Yu.; Goltsev, Anatoliy N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2015)
N/A